The efficacy and safety of intralesional injection of collagenase Clostridium histolyticum for Peyronie’s disease: A meta-analysis of published prospective studies - Zhang, Fuxun; Xiong, Yang; Wang, Wei; Wu, Changjing; Qin, Feng; Yuan, Jiuhong (Frontiers in Pharmacology, 2022)
Background: Peyronie’s disease (PD) is a progressive fibrotic disorder of penis that is adverse to men's health. Currently, effective and reliable non-surgical options for PD are limited. Since the Food and Drug Adminstration (FDA) approved in 2013, intralesional injection of collagenase clostridium histolyticum (CCH) became the only licensed treatment for PD. This meta-analysis aims to evaluate the clinical efficacy and safety of CCH in treating PD, predominantly based on post-FDA studies. Methods: The primary outcome was clinical efficacy evaluated by the percentages of improvement in penile curvature (PC) and Peyronie’s disease symptom bother score (PD bother score). The secondary outcome was the safety assessed by treatment related adverse events (TRAEs). Heterogeneity was assessed by the Cochran’s Q and I2 test. Sensitive and subgroup analysis were performed to explore the source of heterogeneity. Funnel plots and Egger’s test were used to evaluate the publication bias. Results: A total of 11 studies with 1,480 intention to treat population were included. Pooled effect of improvement of PC was 35% (95% CI: 0.33 - 0.38 ), and pooled improvement of PD bother score was 41% (95% CI: 0.37 - 0.45). No heterogeneity was found at pooled improvement of PC (P = 0.845, I2 = 0.00%). Meanwhile, some heterogeneity existed in the pooled improvement of PD bother score (P = 0.069, I2 = 43.4%). The pooled effect of TRAEs was 93% (95% CI 0.88 - 0.97) with significant heterogeneity (P = 0.000, I2 = 92.3%). Conclusions: The intralesional injection of CCH could significantly improve the penile deformity of PD patients. Meanwhile, CCH appears to ameliorate the PD bother score to some extent and have acceptable clinical safety. Future studies are required to clarify the long-term outcomes of CCH injection in treatment of PD.